VASYL STEFANYK’S FIGURE IN THE EVALUATION OF DMYTRO DONTSOV - Markulyak, L. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This article attempts to analyze literary essays of Dmytro Dontsov that are dedicated to the work of Vasyl Stefanyk. It pays attention to the fact that the essayist linked art of Vasyl Stefanyk with existential orientations for European philosophy in the late XIXth – early XXth century. This led to the predominance of the psychological motivation of the characters in Stefanyk’s novellas.